Design & Decorate Interiors - Taylor, Lesley (London New Holland, 2003)
With more than 280 gorgeous color photographs and dozens of fabulous ideas, this is the ultimate home design guide for any budget. Great tips and inspirational decorating suggestions reveal how to work with a room$1 (Bs architectural style, capitalize on its shape and size, and choose colors. Also included are the importance of natural and electric lighting as well as ingenious tricks for revamping existing furniture and fittings.s
Include Index and Colored Illustrations
Keywords: Interior Decoration